2018
DOI: 10.1002/admi.201801274
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Detection of Oxygen Adsorption and Size‐Specific Doping of Few‐Atom Gold Clusters on Graphene

Abstract: COMMUNICATION (1 of 8)properties in graphene, such as (tunable) bandgaps [12] or p-n junctions. [13] Metal atoms and nanoparticles are interesting candidates to tailor graphene. [14] The charge transfer between adparticles and graphene results in tunable (surface) electronic states, which can act as active sites for heterogeneous catalysis, [4,[15][16][17] or enhance the sensitivity and selectivity of graphene gas sensors (see ref.[18] and references therein). Furthermore, metal adparticles are prime candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 63 publications
3
16
0
Order By: Relevance
“…The experimental procedure of depositing few-atom clusters on graphene devices was introduced in previous publications. 26,27 In brief, the electronic measurements were done on a GFET, which consists of a graphene layer deposited on top of a 300 nm SiO 2 layer thermally grown on a heavily doped silicon substrate. When a back-gate voltage V g is applied to the silicon substrate, an electric field induces charge carriers in the graphene strip, changing its resistivity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental procedure of depositing few-atom clusters on graphene devices was introduced in previous publications. 26,27 In brief, the electronic measurements were done on a GFET, which consists of a graphene layer deposited on top of a 300 nm SiO 2 layer thermally grown on a heavily doped silicon substrate. When a back-gate voltage V g is applied to the silicon substrate, an electric field induces charge carriers in the graphene strip, changing its resistivity.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that every deposited Au 3 cluster induces ε e electrons (with ε e > 0, n-doping) and every Au 3 -O 2 complex ε h electrons (with ε h < 0, p-doping) in the graphene strip. 27 Consequently, ε tot the total number of induced electrons in the graphene strip, equals ε e N Au 3 + ε h N Au 3 O 2 , with N Au 3 the number of bare Au 3 clusters and N Au 3 O 2 the number of Au 3 -O 2 complexes. Upon adsorption of one O 2 molecule on a Au 3 cluster, ε tot changes by an amount ε h − ε e = ε O 2 .…”
Section: Doping Of the Graphene Stripmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the few-atom clusters may show metal-coordination atom (N,O)-metal bonds without the direct metal-metal bond. [191][192][193] Notably, different aggregated atom numbers cause a large difference for the geometric and electronic structures, which could be exactly utilized to distinguish the few-atom clusters, nanoclusters and nanoparticles. For example, the few-atom clusters of Au n (2 r n r 7) are characterized by a planar geometric structure (Fig.…”
Section: Fully Exposed Active Sites For Single Atoms and Few-atom Clu...mentioning
confidence: 99%
“…[10,11] 2D materials and their most famous example graphene has attracted enormous worldwide attention and are regarded as a potential candidates for a wide range of applications, including supercapacitors, batteries, catalysis, sensors, wearable electronics, protective coatings, composites, etc. [12][13][14][15][16][17] Graphene, a 2D material in the form of atomically thin sheets composed of carbon atoms that are arranged in a hexagonal array, has many outstanding properties including high electrochemical properties, thermal & optical characteristics, eco-friendliness, high specific surface area, high capacitance, super elasticity and flexibility. [3,18,19] Therefore, graphene could be an ideal platform for energy applications, such as a conductive electrode, high capacity electrode or even as a hydrogen storage.…”
Section: Introductionmentioning
confidence: 99%